The Effectiveness Level Analysis of Flask Less Molding Machine Using Overall Equipment Effectiveness (OEE) as An Improvement of Machine Productivity - Much. Djunaidi; Calvin Athallaric; Hafidh Munawir (Department of Industrial Engineering Universitas Muhammadiyah Surakarta, 2022)
CV. Okabawes Karya Logam is a metal foundry company in Ceper, Klaten, Central Java, Indonesia that uses automatic moulding machines. This company has implemented Total Productive Maintenance which is useful for increasing the overall effectiveness of the company. The use of Flask Less Horizontal Moulding Machine in production to make product moulds is one of the breakthroughs to achieve this effectiveness. However, the usage of the Flask Less Horizontal Moulding Machine cannot be maximized due to several problems. This research was conducted on the Flask Less Horizontal Molding Machine due to the large number of defects and downtime that often occur on machines which aim to measure the value of effectiveness by collecting some supporting data. This research begins by measuring the Overall Equipment Effectiveness (OEE) value, then identifies the root of the problem with the Fishbone Diagram which has 5 main factors that influence it and continues to provide solutions to the five root causes of the problem. The results showed that the Overall Equipment Effectiveness (OEE) value on the Flask Less Horizontal Moulding Machine was 58,53%, this value is below the standard because the Japan Institute of Plan Maintenance (JIPM) set a standard of 85%. There are also 5 main root causes of the Fishbone Diagram identification that have been given solutions.